Development of a consumer experience reporting questionnaire for residential aged care homes in Australia. (23rd April 2019) - Wells, Yvonne; Fetherstonhaugh, Deirdre; Solly, Kane Norman
Abstract : Objective: To develop and pilot a short interview tool to be implemented by the Australian Aged Care Quality Agency (AACQA) in residential aged care, to inform prospective consumers about the quality of care and services received—the consumer experience report (CER). Methods: Twenty‐four questions addressing the four Aged Care Quality Standards were piloted with 140 residents and 48 representatives (including 27 resident‐representative pairs). A method for approximating random selection was also trialled. Fifty‐two residents were interviewed twice, one week apart, and each question's usability was rated by 11 surveyors and two interpreters. Selection criteria for questions included consumer preference, test‐retest reliability, resident‐representative agreement, usability and low missing data. Results: Nineteen questions performed well on missing data, 16 on test‐retest, 17 on resident‐representative agreement and 12 on usability. Ten quantitative and two open‐ended questions were selected. Conclusions: The CER questions proved suitable to collect data systematically on consumer experience in residential aged care. AACQA (now the Aged Care Quality and Safety Commission) uses the CER interview to support their audit process, and aggregated results are published online.